The Effect of Insecticide Application on Plutella xylostella Linn. and its Parasitoid Diadegma sp. - Bambang Tri Rahardjo; Tita Widjayanti; Antika Anggraini (University of Brawijaya, 2021)
Cabbage is one of the commodities that mostly cultivated in Indonesia, but the cabbage farmers often suffered losses because of pests' attack. The important pests on cabbage is Plutella xylostella. This study aimed to investigate the effectiveness level of an insecticide with active ingredient carbaryl 85% in controlling P. xylostella which attacks cabbage and its impact on the parasitoid of Diadegma sp. This research uses a randomized block design with six treatments and four replications. The treatments were different concentrations of the insecticide carbaryl 85%. The testing on Diadegma sp. used two methods, directly and indirectly test (residual exposure). The carbaryl 85% was not effective in controlling P. xylostella, but the population was decreasing. The carbaryl 85% with the highest effect in reducing P. xylostella population was 3.0 g/l. The carbaryl 85% did not affect on the mortality of natural enemies (Diadegma sp. parasitoid) after direct and indirect test.